Expanding the phenotype of hawkinsinuria: new insights from response to N‐acetyl‐L‐cysteine. Issue 6 (3rd August 2016) - Gomez‐Ospina, Natalia; Scott, Anna I.; Oh, Gia J.; Potter, Donald; Goel, Veena V.; Destino, Lauren; Baugh, Nancy; Enns, Gregory M.; Niemi, Anna‐Kaisa; Cowan, Tina M.
Abstract: Hawkinsinuria is a rare disorder of tyrosine metabolism that can manifest with metabolic acidosis and growth arrest around the time of weaning off breast milk, typically followed by spontaneous resolution of symptoms around 1 year of age. The urinary metabolites hawkinsin, quinolacetic acid, and pyroglutamic acid can aid in identifying this condition, although their relationship to the clinical manifestations is not known. Herein we describe clinical and laboratory findings in two fraternal twins with hawkinsinuria who presented with failure to thrive and metabolic acidosis. Close clinical follow‐up and laboratory testing revealed previously unrecognized hypoglycemia, hypophosphatemia, combined hyperlipidemia, and anemia, along with the characteristic urinary metabolites, including massive pyroglutamic aciduria. Treatment with N ‐acetyl‐L‐cysteine (NAC) restored normal growth and normalized or improved most biochemical parameters. The dramatic response to NAC therapy supports the idea that glutathione depletion plays a key role in the pathogenesis of hawkinsinuria.